Pengaruh Model Problem Based Learning (PBL) Berbantuan LKPD terhadap Hasil Belajar Siswa: The Effect of Problem-Based Learning (PBL) Model Assisted by Student Worksheets (LKPD) on Students' Learning Outcomes - Alafiah, Sajinatullaili; Syahidi, Khaerus; Zahara, Laxmi; Yusri, Ahmad (Lembaga Bale Literasi, 2025)
This study aims to determine whether or not there is an effect of the PBL (Problem Based Learning) model assisted by Student Worksheets (LKPD) on student learning outcomes in the elasticity material at MA Mu'allimat NWDI Pancor for the 2022/2023 academic year